2011
DOI: 10.1128/aem.02934-10
|View full text |Cite
|
Sign up to set email alerts
|

Detection of New Francisella-Like Tick Endosymbionts in Hyalomma spp. and Rhipicephalus spp. (Acari: Ixodidae) from Bulgaria

Abstract: We report on the identification of two new Francisella-like endosymbionts (FLEs) found in three different tick species from Bulgaria. The FLEs were characterized by 16S rRNA and tul4 gene sequencing and seem to lack the molecular marker RD1. These two new taxa seem to be facultative secondary endosymbionts of ticks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 19 publications
8
42
3
Order By: Relevance
“…Second, the 16S rRNA-based phylogenetic analysis demonstrated that the FLE from Hyalomma ticks are clustered together as a monophyletic group separated from pathogenic Francisella spp., in agreement with other FLE phylogeny analyses (9,29,33,34), and the phylogenetic congruence between FLE and their Hyalomma hosts is significant. The sequences of FLE from H. marginatum and H. rufipes were identical, as was shown previously (10,29).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Second, the 16S rRNA-based phylogenetic analysis demonstrated that the FLE from Hyalomma ticks are clustered together as a monophyletic group separated from pathogenic Francisella spp., in agreement with other FLE phylogeny analyses (9,29,33,34), and the phylogenetic congruence between FLE and their Hyalomma hosts is significant. The sequences of FLE from H. marginatum and H. rufipes were identical, as was shown previously (10,29).…”
Section: Discussionsupporting
confidence: 73%
“…Our results support the assumption that FLE are obligatory symbionts of their Hyalomma hosts. First, FLE was found to be highly prevalent across all Hyalomma species screened, including H. marginatum, whereas other studies reported lower FLE prevalence (9,29). This difference, however, might be explained by method sensitivity, or the possibility that FLE have a different importance in Hyalomma ticks from different areas.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Recent investigation of 295 dogs for ticks revealed an infestations rate of 23.7 % for ticks, with Rhipicephalus sanguineus and Ixodes ricinus found in 19.7 % and 6.4 % of the dogs respectively, while obviously no Dermacentor reticulatus ticks were identified (Kirkova et al 2013). These data were in part confirmed by another study investigating ticks (n = 472) collected from humans (n = 32), animals (n = 264) and environment (n = 176) in nine major districts in Bulgaria (Ivanov et al 2011). Latter study revealed R. sanguineus in 31.4 % (148/472) and I. ricinus in 25.4 % (120/472) of the cases, but also D. reticulatus was found, even though at a lower rate (3.6 %; 17/472).…”
Section: Introductionsupporting
confidence: 69%
“…To date, a wide range of symbionts, such as Coxiella-like (13), Francisella-like (14), Wolbachia-like (15), Rickettsia-like (16), Arsenophonus-like (17), "Candidatus Midichloria mitochondrii" (18), and Rickettsia peacockii (19) symbionts, have been detected in several tick species. However, little attention has been given to coinfection with multiple symbionts of ticks.…”
mentioning
confidence: 99%